PENILAIAN KUALITAS SARANA PRASARANA LINGKUNGAN DI RUSUNAWA KALIGAWE, KOTA SEMARANG - Megy Utya Khairunisa; Nany Yuliastuti (Jurnal Riptek, 2018)
Kaligawe Flats is one of the social housing in Semarang that located in Kaligawe Village. The provision of this social housing is to decrease the slum area in Semarang and provide a housing for low income people from Semarang City. Along with the passage of time quality of facilities and infrastructure in the area called rusunawa quality decline. This can be seen from some of the damage that occurred. The purpose of this research is to find the existing facilities and infrastructure in Kaligawe Rusunawa area, Semarang City. This study uses a quantitative approach by analyzing the quality and existing facilities. Therefore, the residents of Rusunawa need to be more active in the maintenance which is accompanied by an effort to perform maintenance that is done regularly and periodically to increase the level of facilities and infrastructure quality in Kaligawe Falts.